2018
DOI: 10.1371/journal.pone.0191395
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study to estimate prevalence of periodontal disease in a population of dogs (Canis familiaris) in commercial breeding facilities in Indiana and Illinois

Abstract: The objectives of this cross-sectional study were: 1) to estimate the prevalence and characterize the severity of periodontal disease in a population of dogs housed in commercial breeding facilities; 2) to characterize PD preventive care utilized by facility owners; and 3) to assess inter-rater reliability of a visual scoring assessment tool. Adult dogs (N = 445) representing 42 breeds at 24 CB facilities in Indiana and Illinois were assessed. Periodontal disease was scored visually using the American Veterina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 33 publications
(52 reference statements)
5
46
1
2
Order By: Relevance
“…In a research population of beagles where full-mouth examination was carried out under general anaesthesia and where periodontal disease was defined as clinical attachment loss ≥1 mm, the prevalence of periodontal disease was reported at 20% in one-year old dogs and 84% in dogs over 3 years [62]. A cross-sectional study of dogs in a commercial breeding facility in the USA reported an 86.3% prevalence of periodontal disease using examination of the dentition and gingiva without sedation or anaesthesia [63]. Nonetheless, the results from the current study highlight dental disease as a disorder priority and suggest that attention to increased dental prophylaxis for the Miniature Schnauzer by owners and veterinarians is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In a research population of beagles where full-mouth examination was carried out under general anaesthesia and where periodontal disease was defined as clinical attachment loss ≥1 mm, the prevalence of periodontal disease was reported at 20% in one-year old dogs and 84% in dogs over 3 years [62]. A cross-sectional study of dogs in a commercial breeding facility in the USA reported an 86.3% prevalence of periodontal disease using examination of the dentition and gingiva without sedation or anaesthesia [63]. Nonetheless, the results from the current study highlight dental disease as a disorder priority and suggest that attention to increased dental prophylaxis for the Miniature Schnauzer by owners and veterinarians is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the damage from periodontal disease is not confined to just loss of teeth. Oral infection, especially periodontitis, may affect the course and pathogenesis of a number of systemic diseases, such as chronic bronchitis, pulmonary fibrosis, endocarditis, interstitial nephritis, glomerulonephritis and hepatitis [1].…”
Section: Periodontal Diseasementioning
confidence: 99%
“…Periodontal disease is a significant veterinary health problem of companion dogs [1]. Periodontal disease refers to a group of inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Although one of the most common diseases affecting dogs, with a reported prevalence of 80-89% in dogs over 3 years of age (1)(2)(3)(4), periodontal disease is often overlooked and may therefore be inadequately treated and prevented (5). Periodontal disease is an inflammatory disease affecting the tooth supporting tissues which may lead to progressive tissue and tooth loss (6).…”
Section: Introductionmentioning
confidence: 99%